2020
DOI: 10.3346/jkms.2020.35.e285
|View full text |Cite
|
Sign up to set email alerts
|

National Trends in the Repair of Isolated Superior Labral Tear from Anterior to Posterior in Korea

Abstract: Background: The optimal treatment for superior labral tear from anterior to posterior (SLAP) lesions is controversial. Thus, we aimed to investigate the national surgical trends in isolated SLAP repair in Korea. Methods: We analyzed a nationwide database from the Korean Health Insurance Review and Assessment Service from 2008 to 2017. We investigated the trends in SLAP repair by time, sex, age, and the type of health care institution. Results: From 2008 to 2017, 27,850 isolated SLAP repairs were identified. Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“… 6 Jo et al reported on isolated SLAP repairs in Korea and found that in the last ten years, the SLAP repair incidence rate was approximately 5–8 per 100,000. 17 While Jo et al do not report on the number of diagnoses, we can presume that the diagnosis of SLAP lesions is much higher than the number of SLAP repairs performed. The studies above do not precisely disclose the incidence of SLAP lesions in athletes.…”
Section: Epidemiologymentioning
confidence: 90%
“… 6 Jo et al reported on isolated SLAP repairs in Korea and found that in the last ten years, the SLAP repair incidence rate was approximately 5–8 per 100,000. 17 While Jo et al do not report on the number of diagnoses, we can presume that the diagnosis of SLAP lesions is much higher than the number of SLAP repairs performed. The studies above do not precisely disclose the incidence of SLAP lesions in athletes.…”
Section: Epidemiologymentioning
confidence: 90%
“…9 If symptomatic repair with suture anchors is performed it predictably results in and good to excellent outcomes in over 80% of patients. [10][11][12] Over the past 30 years, numerous studies have reported on the influence of several biomechanical variables for suture anchors that are used to treat shoulder instability. [13][14][15][16][17][18] However, several authors have raised criticism that variation in testing methodology may not allow between study comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the frequency of surgical treatment for this type of SLAP lesions has also increased [7]. However, type 2 SLAP lesion surgeries gradually shifted from arthroscopic repair to biceps tenodesis in the 2010s [7, 8, 15, 17, 21], since the surgical outcomes of arthroscopic SLAP repair failed to meet expectations, and different studies reported variable outcomes [7, 10, 13, 15, 16, 21, 32].…”
Section: Introductionmentioning
confidence: 99%